Keberkesanan Intervensi Membaca Secara Berulang Bersama Rakan Pembaca Terhadap Kefasihan Membaca Murid Bermasalah Pembelajaran - Yuzaila Yusuf; Mohd Mokhtar bin Tahar; Mohd Hairie bin Mohd Nashoha (Universitas Negeri Malang, 2018)
The repeated reading intervention with peers play an important role in enhancing the mastery of the students in reading fluency. This study examines the extent to which the effect of repeating reading intervention programs with peer in improving reading fluency for students with learning disabilities. This study also aims to investigate the effect of implementing repeated reading intervention programs with peers on the reading fluency for student with learning disabilities, seeing the reading fluency when help from peers is eliminated from intervention and identify the challenges and problems faced by peers during this intervention implemented.. The Principles of Social Learning Theory of Bandura and Behaviorism Theory of Thorndike were used in this study along with the model of Automaticity and the Peer Support model. This study is a single subject with multiple design baseline across subjects used to examine the effects of intervention on reading fluency for students with learning disabilities . Three students with learning disabilitiess from Sekolah Menengah Pedas, Rembau were selected as study participants. . The reading texts is provided as an instrument for measuring accuracy and speed which is the main element of reading fluency. During the intervention phase, the study participants are paired with the mainstream students. During the retention phase,repeated reading interventions are still ongoing but without peer help. The results of analysis reveal that repeated reading interventions with peers can enhance the mastery of reading fluency for students with learning disabilities. The findings of this study are expected to assist the Ministry of Education to overcome the problem of reading fluency for students with learning disabilities. In addition,improving achievement and reducing gap between the students with learning disabilities and the mainstream students.